Quality of life and work-life balance among Nurse Educators in the Schools of Nursing in Sri Lanka (International Journal of Nursing Education, 2024)
Objective: The study aimed to assess the quality of life and work-life balance (WLB) among Nurse Educators in the Schools of Nursing in Sri Lanka.Material and Methods: A descriptive cross-sectional study was conducted among 257 Nurse educators in all schools of Nursing in Sri Lanka. Data were collected by using validated and pretested self-administered questionnaires which include Socio-demographic details, a validated quality of life questionnaire (WHO QOL – BREF), and a Work Life Balance assessment scale. Data were analyzed using descriptive and inferential statistics.Results: The overall mean perceived QOL and health of the participants were 3.82 (±0.66) and 3.82 (±0.69) respectively. Participants obtained a high score for the social relationship domain (98.83/100) and a low score for the environmental domain (19.96/100) of the QOL. Findings of the work=life balance revealed an overall mean of 2.87 (SD=1.5) which indicates neither agree nor disagree with work-life interference with personal life and an overall mean of 2.53 (SD=0.96) which indicates neither agree nor disagree with personal life interference with work (PLIW).Conclusions: Nurse educators perceive a moderate level of personal life interference with work, but overall, they acknowledge work/personal life enhancement. These results highlight the complex and multifaceted nature of work-life balance among nurse educators.